URGENSI PUBLIKASI DALAM PENERBITAN KEKAYAAN INTELEKTUAL DI INDONESIA - Herlambang Adhi Nugroho; Ampuan Situmeang; Elsa Syarief (Gorontalo Law Review, 2022)
The similarities between the registered trademark "GEPREK BENSU" and the owners Benny Sudjono and Ruben Onsu necessitates a government strategy to prevent a recurrence. This research focuses on two aspects of the problem: how to publish artificial designs and trademarks in Indonesia, and what is the correct outcome to ensure that fake designs and trademarks in Indonesia are not published in duplicate. To analyze the problem's expression, the author employs a normative legal method. According to the findings, the allocation of fake designs and trademarks is based on early enrolment. To prevent the existence of parallels in society, it is important to disseminate extensively in vivid media.